Multiple gustatory receptors required for the caffeine response in Drosophila. - Lee, Y.; Moon, S.J.; Montell, C. (Proceedings of the National Academy of Sciences of the United States of America, 2009)
The ability of insects to detect and avoid ingesting naturally occurring repellents and insecticides is essential for their survival. Nevertheless, the gustatory receptors enabling them to sense toxic botanical compounds are largely unknown. The only insect gustatory receptor shown to be required for avoiding noxious compounds is the Drosophila caffeine receptor, Gr66a. However, this receptor is not sufficient for the caffeine response, suggesting that Gr66a may be a subunit of a larger receptor. Here, we report that mutations in the gene encoding the gustatory receptor, Gr93a, result in a phenotype identical to that caused by mutations in Gr66a. This includes an inability to avoid caffeine or the related methylxanthine present in tea, theophylline. Caffeine-induced action potentials were also eliminated in Gr93a-mutant animals, while the flies displayed normal responses to other aversive compounds or to sugars. The Gr93a protein was coexpressed with Gr66a in avoidance-gustatory receptor neurons (GRNs), and functioned in the same GRNs as Gr66a. However, misexpression of both receptors in GRNs that normally do not express either Gr93a or Gr66a does not confer caffeine sensitivity to these GRNs. Because Gr93a- and Gr66a-mutant animals exhibit the identical phenotypes and function in the same cells, we propose that they may be caffeine coreceptors. In contrast to mammalian and Drosophila olfactory receptors and mammalian taste receptors, which are monomeric or dimeric receptors, we propose that Drosophila taste receptors that function in avoidance of bitter compounds are more complex and require additional subunits that remain to be identified.